Optimalisasi Skrining HbA1c sebagai Gambaran Rata-Rata Gula Darah 3 Bulan untuk Deteksi Dini Diabetes - Siufui Hendrawan; Alexander Halim Santoso; Bryan Anna Wijaya (Lembaga Pengembangan Kinerja Dosen, 2026)
Diabetes mellitus is a chronic metabolic disorder with a steadily increasing prevalence, often diagnosed at an advanced stage. Glycated hemoglobin (HbA1c) reflects the average blood glucose level over the past three months and serves as a key indicator for early detection of glucose dysregulation. This community service program aimed to optimize HbA1c screening as a simple and effective tool for early diabetes detection within the Baduy community. The activity was conducted using a Point of Care Testing (POCT) approach combined with health education focused on risk factors and diabetes prevention. A total of 59 participants aged 16–75 years underwent HbA1c and fasting blood glucose (FBG) assessments. The mean HbA1c was 4.49 ± 0.6%, and the mean FBG was 97.83 ± 23.21 mg/dL. Based on HbA1c classification, 96.6% of participants were within the normal range, while 3.4% met the criteria for diabetes. According to FBG results, 33.3% were normal, 16.2% prediabetic, and 3.6% diabetic. The prevalence of prediabetes and diabetes was higher among females than among males. An age-related increase in mean glucose levels was observed, indicating reduced insulin sensitivity in older adults. This program not only generated valuable epidemiological data but also enhanced community health literacy and strengthened the role of local health cadres in early disease detection. Community-based optimization of HbA1c screening represents a promising promotive–preventive strategy to reduce the diabetes burden and improve the quality of life in indigenous populations.